The significance of glycated haemoglobin, randomized admission blood glucose, and fasting blood glucose on in-hospital adverse cardiac events in patients with ST-elevation acute myocardial infarction - Anggoro Budi Hartopo; Vina Yanti Susanti; Vita Yanti Anggraeni (Universitas Gadjah Mada, 2022)
In an ST-segment elevation acute myocardial infarction (STEMI), glucose metabolism undergoes disturbance secondary to acute myocardial injury, which affects the clinical outcome during the acute phase. Glucose metabolic disturbance indices are glycated haemoglobin, admission random glucose, and fasting glucose in blood circulation during STEMI. This is a retrospective cohort study, aimed to investigate whether glycated haemoglobin, admission random blood glucose, and fasting blood glucose levels are the risk factors for developing in-hospital adverse cardiac events in STEMI. The result showed that among the three glucose metabolic disturbance indices, fasting glucose was an independent predictor (adjusted OR: 1.010 (95% CI: 1.001-1.018) and the most accurate factor (AUC 64.9 %) for adverse cardiac events. Other glucose metabolic indices, namely random blood glucose and glycated haemoglobin, were associated with increased odds to develop adverse cardiac events but they did not independently predict adverse cardiac events. Therefore, fasting blood glucose was an independent predictor and the most accurate factor for adverse cardiac events in the acute event of STEMI.